Efektifitas Poly Aluminium Chloride (PAC) Pada Pengolahan Limbah Lumpur Pemboran Sumur Minyak - Yustinawati Yustinawati; Nirwana Nirwana; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Handling on waste oil drilling mud in research area uses an integrated sludge waste treatment method known as Mud Centralized Treatment Facility (CMTF). One processing stage performed in CMTF is chemical treatment using aluminum sulfate coagulant where the process of coagulation is optimum yet because there were still contain sediment solids. Poly Aluminium Chloride (PAC) thus becomes an alternative coagulant for the treatment because the main properties of colloidal particles in PAC do coagulation in quickly and optimum pace. Research on the “Effectiveness Coagulant Treatment using Poly Aluminium Chloride on Waste Oil Drilling Mud" aims to evaluate the performance of PAC as coagulant in waste oil drilling mud compare to coagulant Aluminum Sulfate. Jar Test method resulting the optimum conditions of using PAC is on fast stirring speed 140 rpm and slow stirring speed 40 rpm in 6000 ppm (TSS: 84-88%, COD: 62-83% , Oil and grease: 73-75% and NH3: 69-92 %), while using aluminum sulfate in same stirring speed, the optimum result gain in 12,000 ppm (TSS: 34-77% , COD: 36-69% , Oil and grease: 39-55% and NH3: 53-55%). Based on two coagulants test result, the most effective coagulant is using PAC for waste oil drilling mud handling.Key words: Drilling mud, Coagulation, PAC